RADI-15. PERFUSION IMAGING IN PRESUMED PEDIATRIC DIFFUSE INTRINSIC PONTINE GLIOMA: A UK REGIONAL ANALYSIS. Issue 2 (22nd June 2018) - Kilday, John-Paul; Pringle, Catherine; Kamaly-Asl, Ian D; Pizer, Barry; Mallucci, Conor; Hennigan, Dawn; Avula, Shivaram; Cheesman, Edmund; Plessis, Daniel du; Stivaros, Stavros
Abstract: INTRODUCTION: The radiological diagnosis of childhood diffuse intrinsic pontine glioma (DIPG) has historically been founded upon characteristic magnetic resonance imaging metrics. Modern neuro-imaging now incorporates multi-parametric physiological assessments including perfusion and diffusion sequences. Concurrently, histological analysis of presumed DIPGs in the molecular era has resulted in a proportion being re-classified as pontine embryonal tumors; lesions with contrasting management and potential outcomes. We postulated whether integrating modern multi-parametric imaging could discriminate between the two tumors at presentation. METHODS: A retrospective diagnostic MRI analysis of children that had undergone biopsy for presumed DIPG at Manchester and Liverpool Pediatric Neuro-oncology Centers over the last decade was performed. Perfusion was assessed by both arterial spin labeling and dynamic contrast susceptibility weighted techniques. RESULTS: Thirteen patients were identified (median age 4.2 (2.6 – 7.8) years). All lesions had characteristic, non-differentiating T1, T2 and FLAIR appearances, with varying contrast enhancement. Ten were confirmed DIPG (Grade II (3), Grade III (2), Grade IV (4), NOS (1)), while three were embryonal tumors. Reduced perfusion was identified in all embryonal lesions and Grade II DIPGs, whereas increased perfusion was observed in Grade III and IV DIPGs. Diffusion restriction was observed in embryonal lesions compared to Grade II DIPGs. CONCLUSIONS: Low perfusion within a presumed DIPG may reflect a lower grade of glioma or indeed an embryonal pontine tumor, particularly if accompanied by overt intra-lesional diffusion. While requiring validation in larger cohorts, we propose perfusion imaging is a vital adjunct in DIPG radiological phenotyping and should be employed at presentation.